In situ X-ray imaging of pore formation mechanisms and dynamics in laser powder-blown directed energy deposition additive manufacturing. (July 2021) - Wolff, Sarah J.; Wang, Hui; Gould, Benjamin; Parab, Niranjan; Wu, Ziheng; Zhao, Cang; Greco, Aaron; Sun, Tao
Abstract: Directed energy deposition (DED) additive manufacturing (AM) is receiving growing attention in many applications, such as repair, remanufacturing, and fabrication of functionally graded structures. However, the laser-matter interactions and melt pool dynamics in laser DED with powder flow are still unclear, particularly in how pores form and flow inside the melt pool during the process. Understanding the porosity formation mechanisms is critical in the qualification, certification, and overall properties of a DED AM part. Porosity is a common phenomenon and can significantly hinder the quality of DED fabricated parts, as the pores can act as sites of crack nucleation and propagation. Here, we reveal four types of pore formation mechanisms through in-situ and operando high-speed high-resolution X-ray imaging in the DED AM process. Our results confirm that porosity within the feedstock powder induces pores in the process. We also observed pore formation mechanisms unique to the laser-based, powder-blown DED process as a result of powder delivery, keyhole dynamics, melt pool dynamics, and shield gas. High-speed X-ray images provide direct evidence for pore formation mechanisms and show that the pores related to the interaction between the delivered powder and melt pool are the largest in size in laser-based powder-blown DED AM. These results will guide porosity mitigation, elimination, and control in DED AM. Graphical abstract: Image 1 Highlights: Pore formation dynamics in the directed energy deposition (DED) process were directly observed. Pore formation mechanisms unique to the laser-based DED process were revealed. Four types of pore formation mechanisms were reported. The mitigation strategies for each type of pore were provided based on the pore formation analysis. Comparisons were made with pore formation mechanisms in LPBF.